Applications of q-Difference Equation and q-Operator _r Φ_s (θ) in q-Polynomials - Reshem, Faiz A.; Saad, Husam L. (Iraqi Journal of Science, 2024)
We provide a q-operator form solution to a generalized q-difference equation involving (r+s+2)-variables. We introduce a q-polynomials Ψ_n^((A,B)) (x,y,c|q). The generating function, two Rogers formulas, and two types of Srivastava-Agarwal generating functions for the polynomials Ψ_n^((A,B)) (x,y,c|q) are established using the q-difference equation technique.